2009
DOI: 10.1002/ange.200902365
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Producing Pure Single‐Layer Graphene Sheets Based on a Confined Self‐Assembly Approach

Abstract: Kohlenstoff‐Sandwich: Nach der Polymerisation eines pyrrolhaltigen Tensids zwischen zwei Siliciumoxidschichten (siehe Bild; Pyrrolringe in Rot) und anschließendem Carbonisieren und Entfernen der Siliciumoxidtemplate entstehen ausgedehnte Graphen‐Monoschichten. Unter milden Bedingungen sind so μm‐große, reine Graphen‐Schichten im Gramm‐Maßstab zugänglich.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 28 publications
(21 reference statements)
0
43
1
2
Order By: Relevance
“…Graphene nanosheet (GN), a novel planar nanomaterial reported for the first time in 2004,5 has generated great attentions due to its distinct physical properties and potential applications on nanoelectronic devices,6–8 transparent conductors,9, 10 nanocomposites,11, 12 and so on. In this context, extensive researches are being pursued on single‐, bi‐ and few‐layers graphene13–15 as well as graphene oxide (GO) 16, 17. More recently, it is found that the planar structure of GN imparts it excellent capability for the immobilization of a large number of substances, including biomolecules,18 metals,19 drugs,20 fluorescent molecules,21 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene nanosheet (GN), a novel planar nanomaterial reported for the first time in 2004,5 has generated great attentions due to its distinct physical properties and potential applications on nanoelectronic devices,6–8 transparent conductors,9, 10 nanocomposites,11, 12 and so on. In this context, extensive researches are being pursued on single‐, bi‐ and few‐layers graphene13–15 as well as graphene oxide (GO) 16, 17. More recently, it is found that the planar structure of GN imparts it excellent capability for the immobilization of a large number of substances, including biomolecules,18 metals,19 drugs,20 fluorescent molecules,21 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 3 c-e, the deconvolution of the C1 s peak revealed three components centered at 284.9, 285.7, and 286.8 eV, which would be associated with sp 2 carbon atoms, sp 3 carbon atoms, and O-C-O groups. [22] The main component is sp 2 bonded carbon (72.6-74.8 %), whereas sp 3 carbon (21.7-22.3 %) and oxygen groups (3.5-5 %) constitute a small part of graphene sheets. This is consistent with the energy dispersive spectroscopy (EDS) analysis that showed 94.6-97.5 % carbon and 2.5-5.4 % oxygen in HSG…”
mentioning
confidence: 99%
“…The next bands at ~1340 and 1600 cm −1 are characteristic for the D band and G band of GO and reduced GO. G band is common to all sp 2 carbon forms and provides information on the in‐plane vibration of sp 2 ‐bonded carbon atoms .…”
Section: Resultsmentioning
confidence: 99%